Dynamic expression of Notch-dependent neurogenic markers in the chick embryonic nervous system - Ratié, Leslie; Ware, Michelle; Jagline, Hélène; David, Véronique; Dupé, Valérie (Frontiers in Neuroanatomy, 2014)
The establishment of a functional nervous system requires a highly orchestrated process of neural proliferation and differentiation. The evolutionary conserved Notch signaling pathway is a key regulator of this process, regulating basic helix-loop-helix (bHLH) transcriptional repressors and proneural genes. However, little is known about downstream Notch targets and subsequently genes required for neuronal specification. In this report, the expression pattern of Transgelin 3 (Tagln3), Chromogranin A (Chga) and Contactin 2 (Cntn2) was described in detail during early chick embryogenesis. Expression of these genes was largely restricted to the nervous system including the early axon scaffold populations, cranial ganglia and spinal motor neurons. Their temporal and spatial expression were compared with the neuronal markers Nescient Helix-Loop-Helix 1 (Nhlh1), Stathmin 2 (Stmn2) and HuC/D. We show that Tagln3 is an early marker for post-mitotic neurons whereas Chga and Cntn2 are expressed in mature neurons. We demonstrate that inhibition of Notch signaling during spinal cord neurogenesis enhances expression of these markers. This data demonstrates that Tagln3, Chga and Cntn2 represent strong new candidates to contribute to the sequential progression of vertebrate neurogenesis.